2004
DOI: 10.1029/2004jd005166
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal cycles of mixing ratio and 13C in atmospheric methane at Suva, Fiji

Abstract: [1] A series of clean air samples has been collected at a coastal site near Suva, Fiji (18°08 0 S, 178°26 0 E) by researchers at the University of the South Pacific. These samples, covering the period 1994 to mid-2002, have been analyzed for methane mixing ratio and d 13 C and provide the first ever time series of these species reported for this part of the tropical South Pacific. The data show large variability when compared to similar time series of the same species measured farther south in the extratropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The δ 13 C-CH 4 measurements at NIWA are ultimately calibrated against CO 2 produced from NBS-19, IAEA-CO-9 and LSVEC. The long-term δ 13 C-CH 4 records have been presented since then (Lowe et al, 1994(Lowe et al, , 1997(Lowe et al, , 2004Bergamaschi et al, 2001;Schaefer et al, 2016). reported that repeated measurements of the two working reference gases and archived air indicated no detectable drift over 16 years since 1992.…”
Section: Niwamentioning
confidence: 99%
“…The δ 13 C-CH 4 measurements at NIWA are ultimately calibrated against CO 2 produced from NBS-19, IAEA-CO-9 and LSVEC. The long-term δ 13 C-CH 4 records have been presented since then (Lowe et al, 1994(Lowe et al, , 1997(Lowe et al, , 2004Bergamaschi et al, 2001;Schaefer et al, 2016). reported that repeated measurements of the two working reference gases and archived air indicated no detectable drift over 16 years since 1992.…”
Section: Niwamentioning
confidence: 99%
“…2b. Available data, all from the Southern Hemisphere (SH), are also shown: air trapped in polar firn or ice as indicated; air archived at Cape Grim Observatory (Francey et al, 1999); contemporary time series of annual means from Baring Head (updated from Lowe et al, 2004). The KIE value, ε, optimized separately for each source history S&K, E-H v1.3 and E-H v1.4, is −8.1‰, −6.9‰ and −7.4‰ respectively; to these values should be added an adjustment of ∼0.2‰ to "globalise" the SH datasets (see text, Sect.…”
Section: Forward Modelled 13 Chmentioning
confidence: 99%
“…Repeatability based on 10 consecutive analyses of standard air is ±0.05 ‰ or better. δ 13 C-CH 4 values of RHUL are offset corrected by −0.3 ‰ based on intercomparison measurements with NIWA (Lowe et al, 2004).…”
Section: Irms Analysis Of δ 13 C-ch 4 In Bag Samples At Rhulmentioning
confidence: 99%